Analisis Faktor-Faktor Yang Mempengaruhi Kurangnya Integritas Pelayanan Penatua di GKPPD Buluh Tellang - Rohma Oktamala Boangmanalu; Erman Saragih; Haposan Silalahi; Nurelni Limbong; Bestian Simangunsong (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to examine the factors that influence the lack of Integrity of Elder Service in GKPPD Buluh Tellang. This study uses a descriptive qualitative approach method by conducting interviews with elders in GKPPD Buluh Tellang. The results of the study showed that there were two factors influencing elders, namely internal factors and external factors in carrying out service duties in the church, they must have the intention and courage to serve or carry out God's calling so that through the courage of the elders in GKPPD Buluh Tellang they do not forget the eldership received through external factors. pastoral care is very important in increasing the activeness of the elders in carrying out service, so that through interviews that have been conducted by the author that the elders already have an understanding of their goals as elders and with encouragement from external factors the elders carry out their duties and obligations as good servants and are increasing. The conclusion is that it shows that some elders lack confidence in carrying out their duties and responsibilities as servants because there are several things, namely the lack of confidence of the elders in leading worship (not PD), low human resources of the elders, lack of encouragement or motivation and support from the family and the most unpleasant is the political factor.